2020
DOI: 10.1111/eci.13319
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infections in critically ill patients with COVID‐19

Abstract: Background: Little is known about the incidence and risk of intensive care unit (ICU)-acquired bloodstream infections (BSI) in critically ill patients with coronavirus disease 2019 (COVID-19). Materials and methods: This retrospective, single-centre study was conducted in Northern Italy. The primary study objectives were as follows: (a) to assess the incidence rate of ICU-acquired BSI and (b) to assess the cumulative risk of developing ICU-acquired BSI. Results: Overall, 78 critically ill patients with COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
257
4
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(298 citation statements)
references
References 27 publications
22
257
4
15
Order By: Relevance
“…The elevated prevalence of Enterococcus spp. has been highlighted by another study investigating BSI in ICU patients with COVID-19, it is noteworthy that a high percentage of that cohort of patients also received cephalosporins as empirical treatment [28]. The majority of our patients have also received courses of broad spectrum antibiotics, in several cases without a con rmed diagnosis of nosocomial infection, and despite this large antimicrobial coverage we recorded a high incidence of infections.…”
Section: Discussionmentioning
confidence: 65%
“…The elevated prevalence of Enterococcus spp. has been highlighted by another study investigating BSI in ICU patients with COVID-19, it is noteworthy that a high percentage of that cohort of patients also received cephalosporins as empirical treatment [28]. The majority of our patients have also received courses of broad spectrum antibiotics, in several cases without a con rmed diagnosis of nosocomial infection, and despite this large antimicrobial coverage we recorded a high incidence of infections.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, two retrospective cohort studies found that steroid use was associated with detrimental outcome ( Giacobbe et al., 2020 ; Mo et al., 2020 ). The first study included COVID-19 patients who were admitted to the ICU.…”
Section: Resultsmentioning
confidence: 89%
“…The first study included COVID-19 patients who were admitted to the ICU. They found that methylprednisolone use was independently associated with development of a blood stream infection ( Giacobbe et al., 2020 ). Another retrospective cohort study found that patients treated with steroids were less likely to reach clinical and radiological remission within 10 days than patients who did not use steroids ( Mo et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the risk of bacterial infection may be higher in the ICU setting, where more frequent use of vascular and other indwelling devices represent a risk for bloodstream infections (BSI), which are also often reported in patients with COVID-19. 5 Moreover, the use of antiinflammatory agents in the ICU setting, including tocilizumab, was associated with a higher risk of developing BSI, especially when used in combination with methylprednisolone. Considering the lack of convincing evidence on the clinical improvement of critically ill patients treated with IL-6RA, the risks might outweigh the benefits in the critical setting.…”
Section: Replymentioning
confidence: 99%